EP558 Favorable factors of surgical resection for recurrent uterine leiomyosarcoma. (1st November 2019) - Lee, EJ; Kim, HS; Yim, GW; Kim, JW; Park, NH
Abstract : Introduction/Background: The known prognostic factors of uterine leiomyosarcoma (LMS) are initial stage, tumor size, cellular division (mitotic cell count), tumor grade, etc. In LMS, only radically surgical removal offers a chance of long-term survival. Despite complete surgical resection, about 70% develop recurrence within 8 to 16 months after initial diagnosis (even at stage 1 or 2). Even though there are several researches about prognostic factors of recurrent LMS, no definite conclusions that what the prognostic factors for recurrent LMS is. The objective of this research is to evaluate favorable factors of surgical resection for recurrent LMS. Methodology: Clinical and pathological data of 38 patients with recurrent LMS who were treated in one center (Seoul National University Hospital) were analyzed retrospectively to identify prognostic factors for their overall survival (OS) and progression-free survival (PFS). Survival curves were generated using the methods of Kaplan and Meier analysis. Results: The OS was 3.95 years and the median time of first PFS was 17 months and second PFS was 3.4 months. Mitotic count in tumor tissues and time to first recurrence were correlated with OS, but recurrent pattern was more important in time to second recurrence. Localized first recurrent site, solitary recurrence, second recurrent site which was limited in intra-pelvic were significantly associated with longer time to second recurrence. Conclusion: Uterine LMS is a rare disease with extremely poor prognosis. For selected patients who have smaller mitotic count, time to first recurrence, localized and solitary recurrent site, and pelvis-limited second recurrence, secondary cytoreductive surgery can be beneficial and may prolong survival in selected. Disclosure: Nothing to disclose.